Carbapenemase-producing Enterobacteriaceae in hospital wastewater: a reservoir that may be unrelated to clinical isolates. Issue 2 (June 2016) - White, L.; Hopkins, K.L.; Meunier, D.; Perry, C.L.; Pike, R.; Wilkinson, P.; Pickup, R.W.; Cheesbrough, J.; Woodford, N.
Summary: Background: Carbapenemase-producing Enterobacteriaceae (CPE) are an emerging infection control problem in hospitals worldwide. Identifying carriers may help reduce potential spread and infections. Aim: To assess whether testing hospital wastewater for CPE can supplement patient-based screening for infection prevention purposes in a hospital without a recognized endemic CPE problem. Methods: Wastewater collected from hospital pipework on 16 occasions during February to March 2014 was screened for CPE using chromID ® CARBA agar and chromID ® CPS agar with a 10 μg ertapenem disc and combination disc testing. Minimum inhibitory concentrations were determined using British Society for Antimicrobial Chemotherapy methodology and carbapenemase genes detected by polymerase chain reaction or whole-genome sequencing. Selected isolates were typed by pulsed-field gel electrophoresis. Findings: Suspected CPE were recovered from all 16 wastewater samples. Of 17 isolates sent to the Antimicrobial Resistance and Healthcare Associated Infections Reference Unit, six (four Citrobacter freundii and two Enterobacter cloacae complex) were New Delhi metallo-β-lactamase (NDM) producers and the remaining 11 (six Klebsiella oxytoca and five Enterobacter cloacae complex) were Guiana-Extended-Spectrum-5 (GES-5) producers, the first to be described among Enterobacteriaceae in the UK. The four NDM-producing C. freundii, two NDM-producing E. cloacae complex, and four out of five GES-5-producing E. cloacae complex were each indistinguishable isolates of the same three strains, whereas the six GES-5-producing K. oxytoca overall shared 79% similarity. Conclusion: CPE are readily isolated from hospital wastewater using simple culture methods. There are either undetected carriers of CPE excreting into the wastewater, or these CPE represent colonization of the pipework from other sources. Surveillance of hospital wastewater for CPE does not appear helpful for infection control purposes within acute hospitals.